Analysis of land use allocation for sustainable tourism development in Situ Tunggilis, Bogor Regency, Indonesia - Yudi Firmansyah; Rian Nurtyawan; Singgih Irianto; Mohamad Mahfudz; Rina Muthia Harahap; Rudie Rachmat Atmawidjaja; Prambudhianto Putro Pamungkas (Universitas Pakuan, 2025)
The spatial allocation in the buffer zone of Situ Tunggilis is currently not optimal, necessitating a more in-depth analysis to understand the environmental conditions and ecosystem of the area. This spatial allocation analysis can aid in developing effective and sustainable management strategies for the buffer zone. This study aims to analyze land cover in Situ Tunggilis, calculate the area of land cover around its buffer zone, and identify potential opportunities and threats faced by Situ Tunggilis for strategic management. Using aerial photo data from a Mavic 3 Enterprise drone equipped with RTK (Real-Time Kinematic) tools, land cover classification was conducted in the Situ Tunggilis area. The analysis results identified various types of land cover such as open land, recreational areas, residential areas, water bodies, cemeteries, and roads. The buffer zone area of Situ Tunggilis is approximately 17.678 hectares (Ha), predominantly covered by open land at 57.33%, followed by residential areas at 19.3% and fields at 10.7%. The main threat to Situ Tunggilis lies in potential land conversion for residential and agricultural purposes that could reduce water body size and environmental quality; additionally, invasive plant species covering about 13.322 hectares were found on water bodies within Situ Tunggilis that could disrupt ecosystem balance.